SURVEY ON RELIGIOSITY AND SPIRITUALITY OF UNDERGRADUATE STUDENTS (SURVEI TENTANG RELIGIOSITAS DAN SPIRITUALITAS PADA MAHASISWA PROGRAM SARJANA) - Rajagukguk, Robert Oloan (Jurnal Psikologi Indonesia, 2009)
This study was a general survey on religiosity and spirituality of undergraduate students. There has been lack of such studies in Indonesia, despite of its importance in the study of human development and counseling psychology. One hundred and ninety nine male and female students of different religious backgrounds (Catholic, Moslem, and Protestant) participated in the study. Data were gathered using the Faith Development Scale (FDS) and the Survey of Studentsâ Spirituality. Descriptive statistics analysis of the data showed that more first year students have higher level of faith development than final year students and more females have higher level of faith development than male students. Other results indicated that most students do not believe in a Higher Power that controls their lives, have no clear future, and need help in their spiritual growth. Further studies on this area need to be done in order to understand the student as a whole person as well as a spiritual being, in order to be more effective in helping them during their studies in the university and in their personal development.Keywords: spirituality, religiosity, faith development.Penelitian ini merupakan survei mengenai spiritualitas dan keterlibatan religius mahasiswa di Indonesia. Penelitian semacam ini masih sedikit dilakukan dalam konteks Indonesia, padahal sangat penting untuk memperkaya bidang psikologi konseling dan perkembangan. Partisipan penelitian ini adalah 199 mahasiswa universitas swasta dengan latar belakang agama yang berbeda-beda (Katolik, Islam, dan Protestan. Alat pengumpul data meliputi Faith Development Scale dan Survey of Studentsâ Spirituality. Analisis deskriptif data menunjukkan bahwa lebih banyak mahasiswa baru memiliki level of Faith Development lebih tinggi dibandingkan mahasiswa tingkat akhir serta lebih banyak mahasiswi memiliki level of Faith Development lebih tinggi daripada mahasiswa. Temuan lain adalah bahwa kebanyakan mahasiswa maupun mahasiswi tidak percaya tentang adanya suatu Kekuatan Yang Lebih Besar (the Higher Power) yang mengendalikan hidup mereka, tidak memiliki pandangan akan masa depan yang jelas, dan membutuhkan pertolongan untuk bertumbuh secara rohani. Penelitian selanjutnya perlu dilakukan untuk memahami mahasiswa sebagai pribadi yang utuh sehingga selama masa kuliah dapat ditolong secara efektif.Kata kunci: spiritualitas, religiositas, perkembangan iman